2005
DOI: 10.1128/jvi.79.19.12416-12424.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hemagglutinin Glycosylation on Influenza Virus Susceptibility to Neuraminidase Inhibitors

Abstract: The two surface glycoproteins, hemagglutinin (HA) and neuraminidase (NA), of influenza A virus interact with cellular receptors containing terminal neuraminic acid (NeuAc) moieties. HA initiates infection by binding to cellular receptors, whereas NA destroys the receptors by cleaving off NeuAc moieties (49). In addition, HA binds to complementary, as-yetunidentified, cellular receptors that lack NeuAc moieties (5, 46). The functional balance between HA and NA in influenza virus infections has been intensively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 55 publications
1
49
0
Order By: Relevance
“…By using different biochemical approaches, we show that TIZ blocks HA terminal glycosylation at a stage preceding resistance to endoglycosidase H digestion, which is a marker for transport into the cis and middle Golgi compartments (29). Immunomicroscopy studies and analysis of viral particles produced by infected cells confirm that the TIZ-induced alterations impair HA0 trafficking between the endoplasmic reticulum and the Golgi complex, preventing its transport and insertion into the host cell plasma membrane and blocking the exit of mature virions from host cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using different biochemical approaches, we show that TIZ blocks HA terminal glycosylation at a stage preceding resistance to endoglycosidase H digestion, which is a marker for transport into the cis and middle Golgi compartments (29). Immunomicroscopy studies and analysis of viral particles produced by infected cells confirm that the TIZ-induced alterations impair HA0 trafficking between the endoplasmic reticulum and the Golgi complex, preventing its transport and insertion into the host cell plasma membrane and blocking the exit of mature virions from host cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mannose-rich sugar component is processed in the Golgi apparatus during the transport to the cell surface, and terminal glycosylation occurs in trans cisternae of the Golgi apparatus (27). To investigate whether TIZ could affect HA0 passage through the Golgi, we subjected aliquots of radiolabeled proteins and HA0 immunoprecipitated samples to digestion with Endo-H, an enzyme that removes N-linked carbohydrate chains that have not been terminally glycosylated (28) or with PNGase-F, an enzyme that removes all N-glycans (29). As expected, both forms of the protein were sensitive to PNGase-F digestion; however, whereas HA0 from control cells was terminally glysosylated becoming Endo-H-resistant, HA0 from TIZ-treated cells remained sensitive to digestion with the protease up to 4 h after synthesis (Fig.…”
Section: Antiviral Activity Of Thiazolides Against Differentmentioning
confidence: 99%
“…Based on the ability of EB to inhibit viral attachment, we hypothesized that the peptide interacted with either NA or HA since changes to either surface glycoprotein can alter fitness of the virus (22). To determine if EB inhibited NA enzymatic activity, untreated or peptide-treated Tk/Ont was tested for enzymatic activity by MUNANA [2Ј-(4-methylumbelliferyl)-␣-D-N-acetylneuraminic acid].…”
Section: Efficacy In Vivomentioning
confidence: 99%
“…Although glycosylation sites were not necessary for the survival of influenza virus, they played an important role in determining some properties of these viruses. Vasiliy [ see 27,28] reported that a negatively charged glycosylation site near HA RB sites affect HA receptor binding, leading to reduced influenza virus dependence on NA which was the target of antiinfluenza drug failure. Furthermore, the 3 RB sites underwent considerable changes with time.…”
Section: Discussionmentioning
confidence: 99%